SEDIAAN KRIM EKSTRAK AIR BUAH AREN (Arenga pinnata) SEBAGAI ANTIOKSIDAN - Riny Erfiah Rinda; A. Mumtihanah Mursyid; A. Hasrawati (Fakultas Farmasi UMI, 2019)
Palm fruit (Arenga pinnata) contains galactomannan which has the potential as an antioxidant activity with an IC50 value of 20,45 ppm. This study aims to produce cream dosage forms with antioxidant activity using the scaverry DPPH radical scavenger method from arenga pinnata water extract. Palm fruit water extract is formulated in cream form with variations in the concentration of stearic acid and triethanolamine emulgators in F1 (6:4), F2 (7:3), and F3 (8:2). Evaluation of physical stability includes organoleptic testing, homogeneity, pH, emulsion type, viscosity and type of flow carried out before and after forced conditions. In the statistical analysis of viscosity, the results of each formula showed no significant changes both before and after the conditions were forced. The results of the study obtained formula 2 and formula 3 has optimal stability. The stable formula was then tested for antioxidants using the DPPH (1,1-Diphenyl-2-Picrylhydrazyl) radical scavenger method. Formula 2 and formula 3 each yield a DPPH radical inhibition percentage of 65% and 48.04%.